Metformin upregulates circadian gene PER2 to inhibit growth and enhance the sensitivity of glioblastoma cell lines to radiotherapy via SIRT2/G6PD pathway - Li, Hailiang; Ma, Zheng; Yang, Wanfu; Zhang, Yifan; Sun, Jinping; Jiang, Haifeng; Wang, Faxuan; Hou, Li; Xia, Hechun (Frontiers in Pharmacology, 2025)
IntroductionGlioblastoma multiform (GBM) is considered the deadliest brain cancer. Standard therapies are followed by poor patient’s survival outcomes, so novel and more efficacious therapeutic strategies are imperative to tackle this scourge. Metformin has been reported to have anti-cancer effects. However, the precise mechanism underlying these effects remains elusive. A better understanding of its underlying mechanism will inform future experimental designs exploring metformin as a potential adjuvant therapy for GBM. This research aimed to elucidate the potential molecular mechanism of metformin in GBM by integrating proteomics and transcriptomics.MethodsThe study examined the effects of metformin on GBM cell lines using various methods. The U87, U251 and HA1800 were cultured and modified through PER2 knockdown and overexpression. Cell viability was assessed using the CCK8 assay, and G6PDH activity and intracellular NADPH+ levels were measured with specific kits. ROS levels, mitochondrial membrane potential, cell cycle distribution and apoptosis were analyzed by flow cytometry. RNA was extracted for transcriptomic analysis through RNA sequencing, while proteomic analysis was performed on total protein from treated cells. WB detected specific proteins, and RT-qPCR quantified gene expression. In vivo experiments, GBM xenograft on nude mice treated with metformin combining radiotherapy was evaluated and received IHC and TUNEL staining for protein expression and apoptosis assessment. Statistical analyses were conducted using Prism software to identify significant group differences.ResultsWe found that differential expressional genes and proteins relating to circadian rhythm were enriched in proteomic or transcriptomic. The expression of PER2, the key circadian gene, was up-regulated in GBM cell lines when treated with metformin. Furthermore, the expression of silent information regulator 2(SIRT2) was down-regulated, while the expression of the G6PD protein just slightly increased in GBM cell lines. Meanwhile, NADPH+ production and G6PDH enzyme activity significantly decreased. Further study validated that metformin inhibited the cell growth of GBM cell lines through up-regulating PER2 and inhibited SIRT2/G6PD signaling pathway, enhancing radiotherapy(RT) sensitivity. We also found that the inhibition of SIRT2 caused by metformin is mediated by PER2.DiscussionWe found the pivotal role of metformin as an effective circadian rhythm regulator. Targeting circadian clock gene to modify and rescue the dysfunctional circadian clock of GBM cells at molecular level might be an innovative way to administer cancer chronotherapy and maintain metabolic homeostasis in real world practice.